Al-Qaeda's evolution since 9/11. Issue 8 (14th September 2017) - Unknown
Abstract : Although the Islamic State is collapsing in the Middle East, it continues to inspire and assist terrorist attacks in the West, where jihadist terrorism is perceived as a major threat. Al-Qaeda appears to be gaining momentum after a period of relative quiescence, notably in Syria. Hamza bin Laden, Osama bin Laden's son, is a charismatic and increasingly prominent al-Qaeda leader, and is focused on Syria.